PHYTOCHEMICAL ANALYSIS AND IN VITRO DPPH ASSAY OF ETHANOLIC EXTRACT OF MUCUNA PRURIENS SEED - V., SREEKALA; B., VIJAYKISHAN; RAJASEKAR, S. S.; R., RAJESH (International Journal of Current Pharmaceutical Research, 2020)
Objective: To detect the bioactive phytoconstituents of Mucuna pruriens seed extract and to estimate invitro antioxidant activity. Methods: Preliminary phytochemical analysis were done to determine the active phytochemical constituents and DPPH (2, 2-diphenyl-1-picrylhydrazyl) assay method was used for the estimation of In vitro antioxidant activity. Results: Preliminary phytochemical analysis of Mucuna pruriens seed extract showed the presence of chief bioactive components like phenols, flavonoids, tannins, alkaloids, triterpenes and phytosterols. In antioxidant assay, Mucuna pruriens seed extract exhibited a maximum DPPH radical scavenging activity of 72.95% against the standard control with a maximum activity of 93.24% for the same concentration (0.2 mg/ml). This is a clear indication of strong antioxidant property of the drug. Conclusion: Mucuna Pruriens seeds are abundant source of natural antioxidants, and important bioactive phytoconstituents.